The characterization of Ni- and Co-based catalysts for autothermal reforming process - Songip, A. R.; Nasri, N. S.; Latiff, M. H. A. (2004)
A simple technique approach was used to characterize the structural and chemical properties of COO-NiO catalysts supported on 6-AI2O3, HZSM-5 and Mg0-Al203. The morphology of the catalysts was studied by X-Ray diffraction to determine the phase composition and the particle size of thc catalysts. Temperature-programmed reduction (TPR) reveals the formation of NiO and Co30.1 in dependence on temperature in case of catalysts supported on &A1201 and Mg0-A1203 at higher metal loading. The catalysts supported on HZSM-5 also show appearance of NiO. COO and C0~0.4, which could lead to deactivation of the catalysts via formation of coke on the catalyst surface. The formation of Ni0-Coo-Mg0 solid solution supported on MgO-A1203 exhibited stronger interaction between metal and support thus can make the catalysts more resistant to sintering and enhance the structure durability of catalyst in high temperature methane reforming process.